An Experimental Investigation of White Matter Venous Hemodynamics: Basic Physiology and Disruption in Neuroinflammatory Disease - Kolbe, Scott C.; Gajamange, Sanuji. I.; Cleary, Jon O.; Kilpatrick, Trevor J. (Frontiers in Neurology, 2020)
The white matter is highly vascularised by the cerebral venous system. In this paper, we describe a unique blood oxygen-level dependent (BOLD) signal within the white matter using functional MRI and spatial independent components analysis. The signal is characterised by a narrow peak frequency band between 0.05 and 0.1 Hz. Hypercapnia, induced transient increases in white matter venous BOLD that disrupted the oscillation indicative of a vasocontractile mechanism. Comparison of the white matter venous BOLD oscillations between 14 healthy subjects and 18 people with perivenular inflammation due to multiple sclerosis (MS), revealed loss of power in the white matter venous BOLD signal in the peak frequency band (patients = 6.70±0.94 dB/Hz vs controls = 7.64±0.71 dB/Hz; p=0.006). In MS, lower power was associated with greater levels of neuroinflammatory activity (R=-0.64, p=0.006). Using a signal modelling technique, we assessed the anatomical distribution of white matter venous BOLD signal abnormalities and detected reduced power in the periventricular white matter, a region of known venous damage in MS. These results demonstrate a novel link between neuroinflammation and vascular physiological dysfunction in the cerebral white matter, and could indicate enduring loss of vascular compliance associated with imperfect repair of blood-brain barrier damage after resolution of acute neuroinflammation.